Flexible Devices: Extremely Stable Current Emission of P‐Doped SiC Flexible Field Emitters (Adv. Sci. 1/2016) - Chen, Shanliang (Adv Sci (Weinh), 2016)
Novel, P‐doped, flexible SiC field emitters, with both low turn‐on fields and extremely high current emission stability are demonstrated by W. Y. Yang, X. S. Fang, and co‐workers in article number 1500256. The high stability under high temperatures and extreme bending conditions opens up practical applications for SiC field emitters in flexible nanodevices. [Image: see text]